IMPACT OF WEEDS TO SUNFLOWER UNDER ZERO TILLAGE AND PHOSPHORUS FERTILIZATION - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
In order to investigate the effect of no tillage compared with the conventional cultivation and phosphorus fertilization (100, 200 and 300 kg ha-1) P2O5 to the weeds grown in the sunflower field variety Aqmar, a field trial was conducted at the experimental farm (alternative site of College of Agriculture- University of Baghdad) Abu- Ghraib during the spring and fall seasons of 2015. the experiment was carried –out by using R.C.B.D. with in split-split arrangement. The results revealed that un ploughed and un weedy treatments had the lowest means of the dry weight and seeds yield. The results, also revealed a significant increase in the weed density, weed dry weight, seeds yield and its components with the increasing of phosphorus fertilizer from 100 to 300 kg ha-1 in both seasons. It can be concluded, that growing sunflower with was reduced the weed density and its distribution in the field, and this caused to zero weed competition reduction to the crop and consequently increased the seeds yield and its components. However, increased phosphor fertilizer levels raised weeds density, their dry weight and seed yield of sunflower.